Design of resin composites with enhanced physical–mechanical properties. (July 2014) - Wang, R.; Bao, S.; Liu, F.; Jiang, X.; Zhu, M.
Abstract : Novel dental resin composites reinforced with hydroxyapatite (HAP) nanofibres and silica nanoclusters were prepared and the influence of filler compositions on physical–mechanical properties were investigated in this work. HAP nanofibres and silica nanoclusters were fabricated by wet chemical method and the coupling reaction respectively, and then silanised to fabricate resin materials by mixing with dimethacrylate based matrix. The results of XRD pattern, FE-SEM images and FT-TR spectra all confirmed the successful synthesis of HAP nanofibres. Resin composites reinforced with HAP nanofibres and silica nanoclusters as co-fillers showed the reduced polymerisation shrinkage and the enhanced mechanical properties. Among all composites, composite 60∶10 (HAP nanofibres/silica nanoclusters = 60∶10, wt/wt) presented the superior performance, leading to 21% decrease in polymerisation shrinkage, and 13, 55 and 15% enhancement of flexural strength, flexural modulus, and compressive strength respectively, compared with those of composite 0∶60 without HAP nanofibres.